A TOPSIS Approach for Ranking Warmth Service Providers - PK, Parida (International Journal of Computer Sciences and Engineering, 2019)
In the competitive situation, different methods of Multi-criteria decision support have been used to help decision maker select better alternatives for various decision problems. To an economic consideration, there are several criteria needed to be taken into account the temperatures in different cities in the World. According to that base we recorded the temperature in the different months in a city in the year 2018. In this paper, we presented the warmth temperature in the city and crisp temperature of the city by account of the decision making processes. To solve complex real-world decision making problems, multi-attribute decision making (MADM) methods have been developed. The TOPSIS is among the most widely used methods at present which provides valuable outputs in different application areas. With the above hypotheses, calculations involving Eigen vector, square rooting and summations are used for obtaining a relative closeness value of the criteria tested. TOPSIS ranks these values of relative closeness of the whole system by assigning the highest value of the relative closeness to the best attributes in the system. A numerical example given to illustrate the solution process of the suggested approach.